Complicaciones postquirúrgicas en pacientes sometidos a colecistectomía abierta y laparoscópica del Hospital Regional Docente de Trujillo - Ruiz Avalos, Edsel Javier (2019)
Objective: Identify post-surgical complications in post-operative adult patients operated by open and laparoscopic cholecystectomy of the Trujillo Regional Teaching Hospital. Materials and methods: Descriptive, cross-sectional and retrospective study. Clinical records were used with data from adult patients who have undergone cholecystectomy at the Trujillo Regional Teaching Hospital. Results: The main type of surgery was laparoscopic surgery with 77.86%. Female sex prevails with 84.18% of cases. Post-surgical complications occurred in greater proportion in open cholecystectomy, of which the infection 1.22%, was the most prevalent. According to sex, complications were more frequent in females with 60% of cases and males accounted for 40% of cases. Complications were more frequent between the ages of 56 to 65 years with 20% of cases. Conclusions: In the sample studied: post-surgical complications were reported in 2.43% of which they presented more in conventional surgery than in laparoscopic. Cholecystopathies predominate in the female sex and have bibliographic support. Post-surgical complications increase with the patient's age.